(untitled) - Hassan Saleh; Mohsen Kazemi; Mohammad Taher Mirakzehi (پژوهشهای تولیدات دامی)
Extended Abstract Background:In light of recent restrictions on antibiotic use in livestock and poultry feed, producers have shifted towards safer and healthier alternatives such as bacteriophages and acidifiers. This study aimed to explore the impact of these dietary changes on the growth performance, immune response, microbial population, and meat quality of broiler chickens. Methods: The study involved 480 one-day-old male broilers of the Ross 308 strain. The experimental design included six treatments, eight replications, and 20 chickens per replication. The diets tested were a control diet (no additives), a control diet with 40 mg/kg of antibiotic, and diets with 0.5 and 1 g/kg of bacteriophage, and 3 g/kg of two different acidifiers (A and B). At the end of the experiment, two birds from each group were selected for blood tests, meat quality assessment, immune system evaluation, morphology, and gastrointestinal bacteria count. Meat quality was assessed through various parameters including color (L* for lightness, a* for redness, and b* for yellowness), drip loss, water holding capacity, cooking loss percentage, pH, and oxidation. The immune response was evaluated by measuring total antibody titers against SRBC and the sensitivity response to phytohaemagglutinin. The ileal contents of the slaughtered birds were used to estimate the microbial population (E. coli, Lactobacillus, Bifidobacterium spp., Salmonella enterica, and C. perfringens). Intestinal morphology was examined by measuring the crypt depth and the villus height. The pH was also measured in the contents of the ileum and cecum. The data were analyzed using SAS software (2009) in a completely randomized design and the means were compared using Duncan’s multi-range test. Results: Chickens fed on a diet with 1 g bacteriophage per kg diet exhibited the greatest weight gain (p<0.05). Feed consumption and feed conversion ratio remained unaffected by the addition of bacteriophage and acidifiers (p<0.05). Chickens fed on acidifiers (A and B) had the smallest thigh muscle percentage. The highest thymus weight percentage was observed in the groups fed on bacteriophage, while the lowest was observed in the groups receiving acidifiers (p<0.05). However, carcass percentage, breast muscle percentage, relative weight of liver, abdominal cavity fat, spleen, and bursa were not affected by the experimental diets (p<0.05). The water holding capacity of breast meat in chickens fed on acidifiers and bacteriophage was higher than control and antibiotic groups. There was no statistically significant difference in drip loss, cooking loss, and meat pH (45 minutes and 24 hours later) between experimental treatments (p>0.05). On the other hand, the water retention capacity of breast meat of chickens fed with acidifiers and bacteriophage was higher than that of control and antibiotic chickens (p<0.05). The brightness index (L*) of the meat was affected by the experimental diets, with the highest level of L* observed in the meat of the chickens fed with bacteriophage (p<0.05). The effect of experimental treatments on redness (a*) and yellowness (b*) of meat was not significant (p<0.05). Also, the lowest amount of meat oxidation (MDA) was observed in chickens consuming bacteriophage and acidifier A. The humoral immune response (Anti-SRBC titer) of broiler chickens was affected by the experimental diets, but in contrast, the number of red and white blood cells and the blood lymphocyte level were not affected by the experimental treatments. The addition of bacteriophage to the broiler diet improved the immune response and increased the levels of IgM, IgG, and total immunoglobulins in the blood serum (p<0.05). The villus height and crypt depth in both duodenum and jejunum were influenced by the experimental diets (p<0.05). The highest height of duodenum and jejunum villi was observed in the group fed on 1 g bacteriophage/ kg diet and the lowest height of duodenum and geogenome was observed in groups fed with Acidifier A (p<0.05). The highest crypt depth in the duodenum and jejunum was observed in the bacteriophage receiving groups and the lowest crypt depth was observed in the group fed with antibiotics (p<0.05). Villus height/crypt depth index, pH of ileum and cecum contents were not affected by experimental diets. Lactobacillus, Bifidobacteria, Salmonella enteridis and Clostridium perfringens populations were influenced by experimental treatments (p<0.05). The lowest population of the above bacteria was observed in chickens fed with antibiotics. In contrast, the highest number of lactobacillus and bifidobacteria was observed in the group fed on 1 g bacteriophage/kg diet and the highest amount of Salmonella enteridis was observed in the control group (p<0.05). The population of E. coli bacteria and lactic acid producing bacteria (LAB) were not affected by the experimental groups. Conclusion: The use of 1 g bacteriophage/kg diet not only enhanced the growth performance, immune response, and meat quality of broiler chickens, but also led to beneficial changes in intestinal morphology and bacterial population. These results suggest that bacteriophage could be a viable alternative to antibiotics in broiler diets.